CHRITOPHORUS CLP 75 483, MAKADANGANGA. One 10-inch mono disc. Available from Christophorus-Verlag Herder, Herman-Herder-Strasse 4, i.B. D78 Freiburg West Germany (International Library of African Music, 1969)
Boris Konietzko, a dealer in African Arts and Artefacts, has spent many years travelling in Africa. During these years he has learned to understand many African languages and has recorded African music of every description. This Christophorus record is an impressive example of how a representative selection of African Music from the Congo and West Africa, can be successfully edited, from the collection of a single person, onto a 10-inch disc.
Keywords: West Africa; Art Dealer; Belgian Congo; Democratic Republic of the Congo